2017
DOI: 10.1021/acs.biochem.7b00851
|View full text |Cite
|
Sign up to set email alerts
|

Active Site Metal Identity Alters Histone Deacetylase 8 Substrate Selectivity: A Potential Novel Regulatory Mechanism

Abstract: Histone deacetylase 8 (HDAC8) is a well-characterized member of the class I acetyl-lysine deacetylase (HDAC) family. Previous work has shown that the efficiency of HDAC8-catalyzed deacetylation of a methylcoumarin peptide varies depending on the identity of the divalent metal ion in the HDAC8 active site. Here we demonstrate that both HDAC8 activity and substrate selectivity for a diverse range of peptide substrates depends on the identity of the active site metal ion. Varied deacetylase activities of Fe(II)- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…There is a large number of publications about the modulation of HDAC8 enzyme activity by inhibitors or incorporated metal ions [14] , [24] . In particular, the identification of N-acetylthiourea compounds as putative activators of HDAC8 raised considerable attention [25] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a large number of publications about the modulation of HDAC8 enzyme activity by inhibitors or incorporated metal ions [14] , [24] . In particular, the identification of N-acetylthiourea compounds as putative activators of HDAC8 raised considerable attention [25] .…”
Section: Resultsmentioning
confidence: 99%
“…HDAC8 activity is negatively regulated upon phosphorylation by cyclic AMP dependent protein kinase at position serine 39 [13] . Moreover, Fierke et al suggested that HDAC8 could be also regulated by metal switching in vivo [14] . Redox control of epigenetic processes has been proposed as a general principle to allow the cell to adapt to a changing environment.…”
Section: Introductionmentioning
confidence: 99%
“…Protein expression, purification and mutagenesis. BL21(DE3) strain of Escherichia coli cells (New England Biolabs) expressing human HDAC8 were grown at 37°C in~99% D 2 O minimal M9 media containing 15 12 CD 3 )] (for labelling of valine and leucine residues) and 150 mg L −1 of methionine [ 13 C/ 1 H] (for labelling of methionine residues) 1 h prior to induction. Expression was induced at an OD 600nm between 0.5 and 1.0 by 1 mM ITPG.…”
Section: Methodsmentioning
confidence: 99%
“…While HDAC3 is inactive in isolation, it shows significant activity in complex with the SMRT DAD domain 11 . The isozyme HDAC8 is less active than other class I HDACs, however, HDAC8 displays significant activity on its own and also shows enhanced activity in the presence of metals, such as Fe(II) and Co(II) than Zn(II) 12 . HDAC8 was the first human HDAC for which high-resolution crystal structures were published 13,14 .…”
mentioning
confidence: 98%
“…In addition, enzymatic activity patterns of HDACs in cell lysates could be determined (25). Moreover, the same technology enabled the discovery that HDAC8 substrate specificity is dependent on the nature of the metal ion within the active site (26).…”
mentioning
confidence: 99%